Between Theory and Practice: Contributions of the Null Subject Parameter to L2 Teaching - Verniano, Marina (Revista Letras Raras, 2025)
This article shows how knowledge about parametric variation between languages ​​(Chomsky, 1981) can help second language (L2) teachers in the classroom, facilitating the process of L2 acquisition (AL2) by students. Based on the Principles and Parameters Theory (Chomsky, 1981) and research on parametric (re)setting (Ionin et al., 2004; Montrul; Yoon, 2009; Ionin; Montrul, 2010), this paper presents the data collected by Verniano (2022), which show the impacts of planned linguistic input (Marcelino, 2017) on the acquisition of existential sentences in English by children who speak Brazilian Portuguese (BP) as their first language (L1). The data collected by the author demonstrate that solid knowledge about the parametric variation between BP and English, in addition to an effective understanding of the easiest and most difficult structures to acquire, can improve the teacher's performance in the classroom and, consequently, that of their students, corroborating the idea that understanding the Theory of Principles and Parameters can effectively improve L2 teaching.